RELATIONSHIP BETWEEN PERSONAL HYGIENE AND ECHERICHIA COLI BACTERIA ON THE PALM OF CHILDREN'S SDN X IN KEDIRI CITY - Muarofah, Binti; Merlinda , Puput Dinda (UNIVERSITAS AIRLANGGA, 2023)
IntroductionMethod: The design used was cross sectional study. The population was 56. Sampling used Quota Sampling, namely 30 palm swabs from Children at SDN X In Kediri City. In giving scores for Personal Hygiene, a Likert scale was used. Materials used for research were EMB, TSIA, UREA and IMVC media, tools used were coot swabs , incubator, oven and autoclav, personal hygiene variables and Echerichia coli bacteria, research carried out from April to May 2023 Chi-square test analysis using SPSS (Statistical Program For Social Science). The results: 29 samples identified the presence of bacteria and 1 sterile sample, identified bacteria including Salmonella sp (30%) also found Klebsiella sp (20%) and Echerichia coli (47%) bacteria. The personal hygiene of the chindren showed 50% has bad personal hygiene, 43% has good personal hygiene and 7% has very good personal hygiene. As well as showing the presence of Echerichia coli bacteria on the palms of elementary school children. Conclusion A significant relationship was found in the statistical test because the results showed an Asymp.Sig value of 0.000 where the value <0.05 where Ha was accepted and H0 was rejected.